The Process of Economic Transition from Central Planning to a Market Economy: The Former Soviet Union Countries vs China - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
This paper discusses the starting economic, social and political conditions of market-oriented reforms in the former Soviet Union countries and Eastern Europe and compares those to China. In addition, the pace of reforms and their sequencing, as well as their economic and political determinants, are also analyzed. The chapter then proceeds to evaluate the results of reforms in economic and social terms and compares and contrasts the current economic systems in China and in the successor countries of the former USSR. Finally, differences between successor countries of the former USSR in their reform strategies and outcomes are also pointed out, concluding with the forthcoming economic and social challenges in China and successor countries of the former USSR.